AN EVALUATION OF ORGANIZATION EFFECTIVENESS 0F CHILD DEVELOPMENT CENTER UNDER SUBDISTRICT ADMINISTRATIVE ORGANIZATIONS: - - ศรีมารุต เบญจวรรณ; บุญจิตร์ ญาณิศา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
This research aims to study components and indicators for the organization effectiveness of the Child Development Center, to evaluate the organization effectiveness of the Child Development Center under Subdistrict Administrative Organizations based on the balanced scorecard evaluation guideline and to study the appropriate approaches for the Child Development Center management. The research process has done as the follows: studying concept, theory, and related research to synthesize components and indicators of organizational performance evaluation. The focus group discussion conducted among experts to collaborate consider the suitability of components, indicators, and evaluation criteria. Developing the rating-scaled questionnaire that consists of five rates to survey the performance level of the Child Development Centers and this mentioned questionnaire adopt to survey results among the sample group from 392 Child Development Centers. The research methodology includes multiple sampling random method and the data are analyzed using mean and standard deviation. And lastly, studying of the appropriate approaches for the Child Development Center management center by in-depth study at the Child DevelopmentCenters where have the balanced scorecard evaluation results at the level 1-3 and then the data are synthesized and focus group discussion are conducted to evaluate the approaches for the Child Development Center management center by the experts. The research results show as follows: 1. There are four components and 70 indicators for the organization effectiveness evaluation of the Child Development Center as 1) 12 indicators of financial 2) 20 indicators of getting service 3) 30 indicators of internal process, and 4) 8 indicators of learning and development. 2. The organization effectiveness of the Child Development Center rates at the high level in all perspectives. The getting service effectiveness is at the highest level, followed with financial, learning and development, and internal process respectively. 3. The appropriate approaches for the Child Development Center management are financial, getting service, internal process, learning and development.